SARS-CoV-2 Positivity in Early Infancy: A National Cohort From Saudi Arabia - Shaiba, Lana A.; Hadid, Adnan; Altirkawi, Khalid; Alnamnakani, Mahdi A.; Almutayliq, Abdulaziz A.; Alharbi, Areen T.; Hijazi, Asmar M.; AlMoosa, Khalid M.; AlSaud, Nora F.; Murshid, Rozan E.; AlMuhanna, Wejdan S.; Aldawsari, Nasser A.; et al. (Frontiers in Pediatrics, 2022)
Background: Data on SARS-CoV-2 in infants ≤90 days are limited with conflicting reports regarding its presentation and outcomes. Methods: We conducted an ambispective cohort study using prospectively collected Health Electronic Surveillance Network Database by the Ministry of Health, Saudi Arabia. Infants of <90 days of age who had a positive PCR test for SARS-CoV-2 virus were included. Patients were divided in Early neonatal (0-6 days), late neonatal (7-27 days) and post- neonatal (28-90 days) groups were compared for clinical characteristics and outcomes by contacting parents and collecting information retrospectively. Results: Of 1793 infants, 898 infants were included for analysis. Most infants in the early neonatal group had no features of infection (tested based on maternal positivity), whereas most in the late and post- neonatal groups were tested because of clinical features of infection. Fever and respiratory signs were the most common presenting feature in the late and post-neonatal groups. Hospitalization was higher in the early neonatal group (80%), compared to the two other groups. The overall mortality in the cohort was 1.6%. Conclusion: SARS-CoV-2 infection in infants ≤90 days might not be as rare as previously reported. The clinical presentation varies based on age at positive PCR result.